MARKET OF NON-WOOD FOREST PRODUCTS FROM BRAZILIAN SAVANNA - Sandra Regina Afonso (Ciência Florestal, 2009)
In this article, we analyze the main non-wood forest products from Brazilian savanna. We studied the behavior and the growth rates of production and prices of almond of babaçu, oil of copaiba, fiber of buriti, leaf of jaborandi, bark of barbatimão, bark of angico, fruit of mangaba, almonds of pequi, from 1982 to 2005. All the products exhibited decreasing production, with exception of the oil of copaiba and almonds of pequi, which showed positive growth rates: 12.9% and 8.5%, respectively. The analysis of prices for most products was not significant, except for barks of barbatimão and angico, and almonds of pequi, which showed positive trends: 10.9%, 6.7%, and 4.6%, respectively. We believe that results were not significant due to the severe variations of the Brazilian currency in the period. We conclude that pequi is the main product from savanna and that oil of copaiba has the biggest increase in the production because most of the production comes from the whole Brazilian Amazon region.